Acute behavioral interventions and outpatient treatment strategies with suicidal adolescents - O’Brien, Kimberly H. McManama (Int J Behav Consult Ther, 2014)
Despite the prevalence of suicidal thoughts and behaviors among adolescents, there is limited knowledge of effective interventions to use with this population. This paper reviews the findings of studies on behavioral interventions for adolescents who are at acute suicide risk, as well as outpatient treatment and risk management strategies with suicidal adolescents. The importance of addressing comorbid behaviors and enhancing protective factors are discussed. Cultural considerations in working with suicidal adolescents and strategies for conducting culturally competent treatment are explored.